People, Words and Change. Literacy Volunteer Handbook - Bernstein, Judith; Algonquin Coll., Ottawa, Ontario. Adult Basic Education Dept. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
This literacy program guidebook contains specific information for use by volunteer tutors involved in an adult literacy project in Ottawa, Canada, as well as general information on reading instruction techniques, literacy skills, literacy curricula, and resource materials. The origins, objectives, structure, and operations of the Ottawa program entitled "People, Words, and Change" are outlined. A section devoted to volunteer preparation includes a fact sheet and thoughts on adult learning and literacy. Lesson plans, instructional materials, activities, informal reading skill inventories, and basic teaching principles are discussed in a unit on the first lesson. Sight vocabulary, word patterns, phonics, structural analysis, context clues, and language experience are covered in a unit on reading instruction techniques. Topics examined in a unit on literacy skills include recreational reading, study skills, oral reading, handwriting, spelling, grammar, numerical skills, and functional reading. Curriculum selection and organization are described. A discussion of commercial and non-commercial materials is provided. Appendixes include vocabulary lists, a sample self-evaluation, and lists of common reading difficulties and external literacy and related-area contacts. (MN)
Availability: Algonquin College of Applied Arts and Technology, Adult Basic Education Dept., 124 O'Connor St., Ottawa, Ontario K1S 1N3 Canada ($3.00).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Adult Literacy; Adults; Guidelines; Instructional Materials; Learning Activities; Literacy Education; Program Development; Resource Materials; Self Evaluation (Individuals); Teaching Guides; Teaching Methods; Tutorial Programs; Tutors; Volunteers; Guides, Non-Classroom.